2020
DOI: 10.1515/dmdi-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of antitumor necrosis factor therapy in patients with spondyloarthritis

Abstract: ObjectivesTo evaluate the serum dosage of the biomedicine (DBM) and the incidence of antidrug antibody (ADA) against antitumor necrosis factor (TNF) in spondyloarthritis, and to demonstrate the influence of these parameters on the clinical efficiency.MethodsWe conducted a cross-sectional multicentric study including patients with spondylarthritis (SpA) under antiTNF (infliximab [INF], etanercept [ETA] and adalimumab [ADL]) for at least 6 months. A dosage of the ADA and DBM were practiced by the immuno-enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In the different group of our study, RA, SpA and CD, the presence of ADAbs was inversely correlated to the trough levels of IFX and ADA. Similar data have been reported in a large number of studies in the literature [1,3,17,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Immunogenicity Effect On the Residual Level Of The Biologicsupporting
confidence: 87%
See 1 more Smart Citation
“…In the different group of our study, RA, SpA and CD, the presence of ADAbs was inversely correlated to the trough levels of IFX and ADA. Similar data have been reported in a large number of studies in the literature [1,3,17,[23][24][25][26][27][28][29][30][31][32][33].…”
Section: Immunogenicity Effect On the Residual Level Of The Biologicsupporting
confidence: 87%
“…Our results showed that IFX was the most immunogenic biologic (40%) compared to ADA (25%), without a statistically significant difference. Several authors agree that IFX is more immunogenic than ADA [16,17]. This could be explained by the fact that ADA, being a human antibody, is less likely to form ADAbs than IFX which is a chimeric antibody [4].…”
Section: Discussionmentioning
confidence: 99%
“…TDM may help improve the effectiveness of infliximab, a murine monoclonal antibody for which development of ADAs is relatively common. ADAs may develop in 15% to 50% of patients . ADAs may contribute to infusion reactions, subtherapeutic drug levels, and reduced effectiveness …”
mentioning
confidence: 99%
“…In the study by Syversen et al, at 30-week follow-up, the primary end point of clinical remission was achieved in 50.5% (100/198) of patients in the TDM group and in 53% (106/200) of patients in the standard therapy group, with no significant difference between groups. ADA formation in this cohort of patients with mixed disease indications was relatively low (17%-18%), in contrast to other studies in which it was as high as 50% in patients with RA and axial spondyloarthritis, especially among those who did not receive concomitant immunomodulators such as methotrexate …”
mentioning
confidence: 99%